Ultrasound targeted microbubble destruction-mediated SOCS3 attenuates biological characteristics and epithelial-mesenchymal transition (EMT) of breast cancer stem cells. Issue 2 (1st February 2022) - Tang, Xiaojiang; Hao, Na; Zhou, Yuhui; Liu, Yang
ABSTRACT: SOCS3 is low-expressed in breast cancer and may be a potential target. Ultrasound targeted microbubble destruction (UTMD) improved the efficiency of gene transfection. We explored the effects of UTMD-mediated transfection of SOCS3 on the biological characteristics and epithelial-mesenchymal transition (EMT) of breast cancer stem cells (BCSCs). The expression of SOCS3 in breast cancer (BC) and its association with prognosis were evaluated by GEPIA and The Cancer Genome Atlas (TCGA) websites. BCSCs were sorted by flow cytometry and immunomagnetic bead method, followed by sphere formation, 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and xenograft assays to test their effects in vitro and in vivo . The levels of SOCS3, EMT- and STAT3 pathway-related genes were determined by RT-qPCR and Western blot, respectively. The effects of liposome and UTMD on BCSCs and mice were compared by the gain-of-function experiments. Low expression of SOCS3 was associated with poor prognosis of BC patients, and found in BC and BCSCs. BCSCs were successfully sorted, with high viability and tumorigenicity. UTMD increased the transfection rate of SOCS3. Moreover, UTMD- and liposome-mediated SOCS3 reduced cell viability, proliferation, migration and invasion, blocked cell cycle, inhibited sphere formation in BCSCs, and retarded tumor growth in mice. Mechanistically, overexpressed SOCS3 inhibited the expressions of EMT-related genes and the activation of STAT3 pathway in BCSCs and mice. The regulatory effects of UTMD-mediated SOCS3 on the above-mentioned biological characteristics were better than liposome-mediated SOCS3. UTMD-mediated SOCS3 has a better therapeutic effect in BC, providing new experimental evidence for the treatment of BC. Graphical abstract: uf0001